Thinking Freedom in Africa : Toward a theory of emancipatory politics - Neocosmos, M. (Book collections on Project MUSE., 2018)
Previous ways of conceiving the universal emancipation of humanity have in practice ended in failure. Marxism, anti-colonial nationalism and neo-liberalism all understand the achievement of universal emancipation through a form of state politics. Marxism, which had encapsulated the idea of freedom for most of the twentieth century, was found wanting when it came to thinking emancipation because social interests and identities were understood as simply reflected in political subjectivity which could only lead to statist authoritarianism. Neo-liberalism and anti-colonial nationalism have also both assumed that freedom is realisable through the state, and have been equally authoritarian in their relations to those they have excluded on the African continent and elsewhere.